PEMBERDAYAAN CALON LEGISLATIF DI TAHUN POLITIK - Wakidul Kohar, Nurrohman Zulkarnain, Awis Karni (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2019)
This research departs from the term 4D (coming, sitting, silent and money) that is raised by individual communities towards legislators in general who tend to be less dignified and from this it is necessary to empower legislative candidates consisting of empowering monotheistic creeds and empowering skills. This research is a qualitative research by giving an overview as it exists and happens to the object of research. Then the research informants are legislative candidates, executors of empowerment activities and administrators of the Padang City Prosperous Justice Party DPD. Data was collected through interviews and subsequently analyzed qualitatively using the model proposed by Miles and Huberman. The results showed that the legislative candidates for the Padang City Prosperous Justice Party registered with the Padang City KPU were divided into two types, namely the internal and external legislative candidates whose recruitment was based on cadre aspirations from the DPRa, DPC to DPD levels and approved by the central leader of the Prosperous Justice Party. The program of empowerment of monotheism is carried out by the DPD of the Padang City Prosperous Justice Party in the political year is a differentiator between the cadres of the Prosperous Justice Party and other party members who are not Islamic-based.